2022
DOI: 10.3390/vetsci9110598
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Dynamics of Circulating Steroid Hormones in Mule and Equine Neonates

Abstract: It is necessary to study hormonal patterns from mules to recognize alterations and neonatal maladaptation. Our objective was to evaluate concentrations of hormones in mule (n = 6) and equine foals (n = 6). Blood was collected at T0, 1, 6 and 12 h after birth. Hormone concentrations were evaluated using liquid chromatography tandem mass spectrometry. Effects of time, group and interactions and regression analysis were evaluated (p < 0.05). There was a cubic and quadratic decline in mule and equine foals, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A recent study [14] found physiological differences between horse and mule neonates, such as a lower concentration of the steroid 3β,20α-dihydroxy-DHP, which may be related to the placental steroidogenic capacity during hybrid gestation. A higher APGAR value was also observed in mules when compared to horse foals [14], probably due to the release of progestogens in the perinatal period. These differences suggest that mule foals' metabolism is derived from different origins, presumably placenta, gonads, and adrenals, indicating that the endocrinology of mules is different and perhaps that they undergo distinct aspects of adaptation during the first days of life.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study [14] found physiological differences between horse and mule neonates, such as a lower concentration of the steroid 3β,20α-dihydroxy-DHP, which may be related to the placental steroidogenic capacity during hybrid gestation. A higher APGAR value was also observed in mules when compared to horse foals [14], probably due to the release of progestogens in the perinatal period. These differences suggest that mule foals' metabolism is derived from different origins, presumably placenta, gonads, and adrenals, indicating that the endocrinology of mules is different and perhaps that they undergo distinct aspects of adaptation during the first days of life.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, these biomarkers are important as they are one of the central elements in signal transduction pathways involved in cell proliferation, differentiation, and apoptosis [13]. A recent study [14] found physiological differences between horse and mule neonates, such as a lower concentration of the steroid 3β,20α-dihydroxy-DHP, which may be related to the placental steroidogenic capacity during hybrid gestation. A higher APGAR value was also observed in mules when compared to horse foals [14], probably due to the release of progestogens in the perinatal period.…”
Section: Introductionmentioning
confidence: 99%